2007
DOI: 10.1111/j.1467-8624.2007.00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant Joint Attention, Temperament, and Social Competence in Preschool Children

Abstract: Infant joint attention has been observed to be related to social-emotional outcomes in at-risk children. To address whether this relation is also evident in typically developing children, 52 children were tested at 12, 15, 24, and 30 months to examine associations between infant joint attention and social outcomes. Twelve-month initiating and responding to joint attention were related to 30-month social competence and externalizing behavior, even when accounting for 15-month temperament ratings, 24-month cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
3
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(120 citation statements)
references
References 87 publications
5
97
3
5
Order By: Relevance
“…In typical development, recent evidence suggests that IJA and RJA are mostly independently developing skills (Mundy et al, 2009;Slaughter & McConnell, 2003;Striano, Stahl, & Cleveland, 2009;Vaughan Van Hecke et al, 2007). However, in this study, a significant correlation was found between the IJA and RJA skills of children with ASD, which is in line with the results of some other studies in young children with ASD (e.g., Bono, Daley, and Sigman, 2004;Dawson et al, 2004;Siller andSigman, 2008, Toth, Munson, Meltzoff, Dawson, 2006).…”
Section: Initiation Of Joint Attention Skillssupporting
confidence: 91%
See 1 more Smart Citation
“…In typical development, recent evidence suggests that IJA and RJA are mostly independently developing skills (Mundy et al, 2009;Slaughter & McConnell, 2003;Striano, Stahl, & Cleveland, 2009;Vaughan Van Hecke et al, 2007). However, in this study, a significant correlation was found between the IJA and RJA skills of children with ASD, which is in line with the results of some other studies in young children with ASD (e.g., Bono, Daley, and Sigman, 2004;Dawson et al, 2004;Siller andSigman, 2008, Toth, Munson, Meltzoff, Dawson, 2006).…”
Section: Initiation Of Joint Attention Skillssupporting
confidence: 91%
“…Following Mundy et al (2007), the frequency of the following IJA behaviours was observed: 1) making eye contact with the examiner while manipulating a toy, 2) alternating eye contact between an active mechanical toy and the tester, 3) pointing to an active mechanical toy with or without eye contact, and 4) showing by raising objects toward the tester's face with eye contact. The former two were combined into a Basic IJA low score, the latter two were combined into a Basic IJA high score.…”
Section: (Insert Figure 1 Here)mentioning
confidence: 99%
“…For example, longitudinal studies show that infants' skills in sharing attention with others are correlated with their later social competence [Charman et al, 2000;Vaughan Van Hecke et al, 2007] and with cognitive and language development [Baldwin, 1995;Brooks & Meltzoff, 2008;Carpenter, Nagell, & Tomasello, 1998;Mundy et al, 2007;Vaughan Van Hecke et al, 2007]. However, this relation does not seem to hold in children with Williams syndrome [Laing et al, 2002], and the absence of pointing, particularly the lack of pointing to direct attention, at 18 months, is associated with the later diagnosis of autism [Baron-Cohen, Allen, & Gillberg, 1992;Baron-Cohen et al, 1996].…”
mentioning
confidence: 99%
“…Joint attention skills are important because they are considered early markers of social cognitive development; that is, they reflect the early development of the infant's ability to think about the perspective of another individual (Tomasello 1995). These skills are critical to social learning and social information processing (Mundy and Jarrold 2010), language development (Sigman and Kasari 1995), and the emergence of social and behavioral competence in childhood (Vaughan Van Hecke et al 2007). …”
Section: Predictors Of Adult Independencementioning
confidence: 99%